Corticotomy-assisted maxillary protraction with skeletal anchorage and Class III elastics - GARİP, HASAN; YILMAZ, HANİFE NURAY (E H ANGLE EDUCATION RESEARCH FOUNDATION, INC, 2015)
Objective: To analyze the treatment effects of corticotomy-assisted maxillary protraction with skeletal anchorage and Class III elastics in patients with Class III malocclusions. Materials and Methods: The study group consisted of 19 patients with a mean age of 13.12 +/- 1.28 years. Initially, patients were monitored for 5 months before treatment to evaluate growth changes. Changes during control, protraction and fixed orthodontic treatment periods were compared with the cephalometric radiographs taken initially, before protraction, after protraction, and after fixed orthodontic treatment. Treatment outcomes also were compared with the growth effects. Results: Sagittal measurements of maxilla showed significant improvements (3.59 +/- 1.32 mm) during the protraction period (3.85 +/- 1.12 months) whereas no significant changes were seen during the control period. Upper and lower incisor inclinations were increased, and the upper occlusal plane angle showed significant counterclockwise rotation during protraction. Significant soft-tissue changes also reflected the underlying skeletal changes. Maxillary advancement was stable during fixed orthodontic treatment. Conclusion: Compared with control period of the patients, this protocol produced significant improvements in skeletal and soft-tissue structures.
Keywords: Elastics; Maxillary protraction; Skeletal anchorage; FACE MASK THERAPY; CLEFT-LIP; EXPANSION; MALOCCLUSION; DISTRACTION; IMPLANTS; SURGERY; SUCCESS; PALATE